2017
DOI: 10.1016/j.cogpsych.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Grounding principles for inferring agency: Two cultural perspectives

Abstract: The present research investigates cultural variation in grounding principles for inferring agency in order to address an important theoretical debate: does cultural diversity in agency concepts reflect an animistic overextension of (universal) folkpsychology, as many have argued, or an alternative theory of folkcommunication based on relational principles? In two experiments, mind perception measures were adapted to assess beliefs concerning the agency of non-animal kinds (plants, abiotic kinds, complex artifa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 61 publications
1
32
0
1
Order By: Relevance
“…Our initial analyses took a broad look by collapsing across the specific capacities (thought, desire, etc.) for an overall measure of “agency.” As predicted, results from several experiments have shown that Ngöbe are more likely than US participants to attribute agency to plants and abiotic kinds based on their capacity to interact with the environment, as compared to US participants who are relatively more likely to attribute agency to complex artifacts due to their human‐designed information processing capacities (Ojalehto, Medin, and Garcia 2017a; Ojalehto, Medin, and Garcia 2017b) (see Figure 1). 3 Looking within the Ngöbe results more closely, we see that plants are ascribed agency at levels closer to that of animals than artifacts, suggesting that agency is seen as a shared property of vegetal and animal kinds.…”
Section: Current Research: Cognitive Psychological Studies On the Newmentioning
confidence: 60%
See 1 more Smart Citation
“…Our initial analyses took a broad look by collapsing across the specific capacities (thought, desire, etc.) for an overall measure of “agency.” As predicted, results from several experiments have shown that Ngöbe are more likely than US participants to attribute agency to plants and abiotic kinds based on their capacity to interact with the environment, as compared to US participants who are relatively more likely to attribute agency to complex artifacts due to their human‐designed information processing capacities (Ojalehto, Medin, and Garcia 2017a; Ojalehto, Medin, and Garcia 2017b) (see Figure 1). 3 Looking within the Ngöbe results more closely, we see that plants are ascribed agency at levels closer to that of animals than artifacts, suggesting that agency is seen as a shared property of vegetal and animal kinds.…”
Section: Current Research: Cognitive Psychological Studies On the Newmentioning
confidence: 60%
“…We hypothesized that Ngöbe would attribute agency based on a folktheory of communication where the constructs revolve around relationships, interactions, and signs, whereas US participants would rely on a mentalistic folkpsychology that revolves around minds, mental states, and interior consciousness. To assess this, we developed a coding scheme to analyze participants’ verbal explanations for constructs associated with each hypothesized cultural folktheory (details in Ojalehto, Medin, and Garcia 2017b, 2015a).…”
Section: Current Research: Cognitive Psychological Studies On the Newmentioning
confidence: 99%
“…The splitting of human agency into agency‐other and agency‐self, as show in the Fijian samples, may reflect a relational understanding of mind—that mind exists in the space between people rather than just within an individual (see ojalehto et al., ). This emphasis on a relational, sociocentric model of self is important throughout the Pacific (Airni, Anae, & Mila‐Schaaf, ; Anae, ; Brison, ; Poltorak, ) and may be filtering into the processes of how people conceive of minds that we measure here.…”
Section: Discussionmentioning
confidence: 99%
“…There are some existing psychological studies that show that both culture and religious beliefs can affect how individuals reason about minds. Work with the Ngöbe people of Panama has found that the Ngöbe use ecological and social relationships, rather than animacy and consciousness, as a basis for agency (ojalehto et al., ,b). This is illustrated by the finding that the Ngöbe include plants and abiotic entities in their category of things that have agency and a capacity for intentional actions along with animals or humans.…”
Section: Cultural Differences In Conceiving Of and Reasoning About Mindsmentioning
confidence: 99%
See 1 more Smart Citation